2015
DOI: 10.1007/s00203-015-1118-z
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Phaseolus vulgaris with the nodule-endophyte Agrobacterium sp. 10C2 affects richness and structure of rhizosphere bacterial communities and enhances nodulation and growth

Abstract: Agrobacterium sp. 10C2 is a nonpathogenic and non-symbiotic nodule-endophyte strain isolated from root nodules of Phaseolus vulgaris. The effect of this strain on nodulation, plant growth and rhizosphere bacterial communities of P. vulgaris is investigated under seminatural conditions. Inoculation with strain 10C2 induced an increase in nodule number (+54 %) and plant biomass (+16 %). Grains also showed a significant increase in phosphorus (+53 %), polyphenols (+217 %), flavonoids (+62 %) and total antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…The taxonomy and classification of Agrobacterium are, however, questioned, and there are many disagreements regarding the nomenclature of Agrobacterium species as well as the genus. Most species have been controversially reclassified as Rhizobium species (Farrand et al 2003 ; Chihaoui et al 2015 ). Strains of Agrobacterium genus may be either tumorigenic, rhizogenic or non-pathogenic depending on the type of plasmids they comprise (Chihaoui et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomy and classification of Agrobacterium are, however, questioned, and there are many disagreements regarding the nomenclature of Agrobacterium species as well as the genus. Most species have been controversially reclassified as Rhizobium species (Farrand et al 2003 ; Chihaoui et al 2015 ). Strains of Agrobacterium genus may be either tumorigenic, rhizogenic or non-pathogenic depending on the type of plasmids they comprise (Chihaoui et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most species have been controversially reclassified as Rhizobium species (Farrand et al 2003 ; Chihaoui et al 2015 ). Strains of Agrobacterium genus may be either tumorigenic, rhizogenic or non-pathogenic depending on the type of plasmids they comprise (Chihaoui et al 2015 ). Numerous reports have revealed that Agrobacterium strains recovered from the root nodules have not shown ability to re-nodulate the original hosts, thus reported as nonsymbiotic (Wang et al 2006 ; Liu et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they can increase nutrient (mainly P and Fe) availability in the root zone (Chebotar et al 2001;Argaw 2012), inhibit phytopathogens (Tavares et al 2018) and modify rhizosphere chemicals, such as ethylene (Nascimento et al 2018). The use of NER can significantly increase the ability of rhizobia resident in soil to form nodules, fix N and increase growth in soybean, Glycine max (Dashti et al 1998), mung bean (Shaharoona et al 2006), chickpea, Cicer arietinum (Abdiev et al 2019) and common bean (Chihaoui et al 2015). Likewise, the use of a NER, Azospirillum brasilense, inoculated in combination with elite rhizobial strains can increase nodulation and amount of fixed N derived from symbiosis in soybean (Hungria et al 2015), common bean, Phaseolus vulgaris (Remans et al 2008) and lentil, Lens culinaris (Tsigie et al 2011).…”
Section: Legume-rhizobia-pgpr Interactionsmentioning
confidence: 99%
“…probiotics) to achieve a desired host effect is now widespread, true microbiome engineering studies remain rare. Diverse examples of successful probiotic studies include: increased biomass and antioxidant capacity in plants inoculated with Agrobacterium (Chihaoui et al, 2015), reduced white pox disease in corals that received a probiotic cocktail of 13 bacterial strains isolated from coral mucus (Alagely et al, 2011), and intestinal epithelial cells with increased ability to keep pathogens from escaping the intestinal tract in mice that were administered Lactobacillus strains (Mack et al, 2003). While often successful, probiotic approaches typically rely on relatively simple manipulations of the microbiome by introducing known and culturable bacterial species.…”
Section: Introductionmentioning
confidence: 99%